CD26/DPPIV and response to hepatitis B vaccination - Dourado, Marília (2004)
The prevention of hepatitis B is important, since it is responsible for significant morbidity and mortality around the world. Unfortunately, hepatitis B vaccine does not always induce protective immunity. The lack of immune response to vaccine (non-responders) can depend on individual characteristics.